MORPHOLOGICAL AND MORPHOPHONEMIC PROCESS (NATURE, TYPES, AND RULES) - Nurhayati, Dwi Astuti Wahyu (Pusat Pengembangan Bahasa IAIN Tulungagung, 2011)
Morphology or morphemic is defined as the study of the morpheme and their arrangements in building new larger morphological constructions. Morph is a physical form representing some morpheme in a language. Morpheme is the minimal unit of linguistics in a certain language. Seeing from the word formation, a new word in English and the change form of morpheme can be analyzed through two main processes. The morphological process has two main types of processes, affixation and non affixation. Affixation consists of two processes, (1) internal change, (2) Zero Modification. Affixation has ten processes namely (1)compounding, (2) blending, (3) borrowing, (4) coinage, (5) clipping, (6) backformation, (7) conversion (8) acronym, (9) multiple process (10)Reduplication. Morphophonemic processes are classified into ten processes, namely (1) loss of phonemes, (2) addition of phonemes, (3) simple consonant change, (4) assimilation; (5) dissimilation; (6) synthesis; (7) change of syllabic vowel or diphthong; (8) gradation; and (10) suppletion. This article tries to describe the process which should be conducted to analyze the word formation through morphological and morphophonemic processes.